Intracranial meningioma, mimicking brain metastasis on (18)F sodium fluoride bone scan in a case of carcinoma cervix - Priya, Rollapeta Ramya (Indian J Nucl Med, 2016)
Bone scintigraphy (BS) is a well--established commonly used imaging modality for staging and follow--up evaluation of cancer patients. Occasionally, BS may show asymptomatic unusual extraosseous lesions in the body which may or may not be related to primary disease. We here present an interesting case of carcinoma cervix in whom (18)F sodium fluoride positron emission tomography-computerized tomography (PET-CT) bone scan detected an intracranial lesion. Initially, this lesion was suspected as brain metastasis; however, later on, combined PET--CT images and contrast-enhanced CT confirmed this lesion as calcified falcine meningioma in the right posterior parietal region.